Chronic ciprofloxacin and atrazine co-exposure aggravates locomotor and exploratory deficits in non-target detritivore speckled cockroach (Nauphoeta cinerea) (2021)
The global detection of ciprofloxacin and atrazine in soil is linked to intensive anthropogenic activities in agriculture and inadvertent discharge of industrial wastes to the environment. Nauphoeta cinerea is a terrestrial insect with cosmopolitan distribution and great environmental function. The current study probed the neurobehavioral and cellular responses of N. cinerea singly and jointly exposed to atrazine (1.0 and 0.5 μg g−1 feed) and ciprofloxacin (0.5 and 0.25 μg g−1 feed) for 63 days. Results demonstrated that the reductions in the body rotation, maximum speed, turn angle, path efficiency, distance traveled, episodes, and time of mobility induced by atrazine or ciprofloxacin per se was exacerbated in the co-exposure group. The altered exploratory and locomotor in insects singly and jointly exposed to ciprofloxacin and atrazine were verified by track plots and heat maps. Furthermore, we observed a decrease in acetylcholinesterase and anti-oxidative enzyme activities with concomitant elevation in the levels of lipid peroxidation, nitric oxide, and reactive oxygen and nitrogen species were significantly intensified in the midgut, hemolymph, and head of insects co-exposed to ciprofloxacin and atrazine. In conclusion, exposure to binary mixtures of ciprofloxacin and atrazine elicited greater locomotor and exploratory deficits than upon exposure to the individual compound by inhibiting acetylcholinesterase activity and induction of oxido-inflammatory stress responses in the insects. N. cinerea may be a usable model insect for checking contaminants of ecological risks.